(untitled) (Global Journal of Human-Social Science, 2013)
In this play Thorns on a Canvas Asif Currimbhoy tries to show the relationship between an elite patron of the Art academy and the poor artists like Yakoob and Nafisa He also depicts the pathetic condition of the artists especially of those who are true and honest in their work Through some characters he reveals the same He has also written about the Art academies which are alike a shop now a day Through this play he shows the relationship is a variation of colonizers colonized syndrome